PENGEMBANGAN BUKU CERITA BERGAMBAR MATERI BANGUN DATAR BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA SD ISLAM BANI HASYIM - Azahra, Dila Fitri (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The development of a picture storybook based on ethnomathematics of traditional houses was carried out to improve the mathematical literacy of first-grade students at SD Islam Bani Hasyim, specifically on the topic of flat shapes. The book was designed as a contextual learning medium that incorporates local cultural elements such as traditional houses: Joglo Bucu, Bapang, Tengger, and Lopo Boti. This research used the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were students from class I-B. Data collection techniques included interviews, validation questionnaires (from media, material, language, and instructional experts), pre-tests and post-tests, and student response questionnaires. The data were analyzed both qualitatively and quantitatively. Validation results showed scores of 84.29% (media expert), 71.67% (material expert), 81.43% (language expert), and 90% (instructional expert). Student responses reached 94.8% in the small group trial and 90.73% in the large group trial. The average student score increased from 56.09 (pre-test) to 82.04 (post-test). Improvements were also evident in the mathematical literacy indicators: formulating information (increased by 11%), applying strategies (17%), and interpreting solutions (16%). It can be concluded that the ethnomathematics-based picture storybook is highly valid, practical, and effective in improving students’ mathematical literacy. ABSTRAK Pengembangan buku cerita bergambar berbasis etnomatematika rumah adat dilakukan untuk meningkatkan literasi matematis siswa kelas I SD Islam Bani Hasyim pada materi bangun datar. Buku dikembangkan sebagai media pembelajaran kontekstual yang memuat unsur budaya lokal, seperti rumah adat Joglo Bucu, Bapang, Suku Tengger, dan Lopo Boti. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian adalah siswa kelas I-B. Teknik pengumpulan data meliputi wawancara, angket validasi (ahli media, materi, bahasa, dan pembelajaran), pre-test dan post-test, serta angket respon siswa. Data dianalisis secara kualitatif dan kuantitatif. Hasil validasi menunjukkan skor sebesar 84,29% (ahli media), 71,67% (ahli materi), 81,43% (ahli bahasa), dan 90% (ahli pembelajaran). Respon siswa pada uji coba kelompok kecil memperoleh skor 94,8%, dan pada kelompok besar sebesar 90,73%. Nilai rata-rata siswa meningkat dari 56,09 (pre-test) menjadi 82,04 (post-test). Peningkatan juga terlihat pada indikator literasi matematis: merumuskan informasi (naik 11%), menerapkan strategi (naik 17%), dan menafsirkan solusi (naik 16%). Dapat disimpulkan bahwa buku cerita bergambar berbasis etnomatematika rumah adat sangat valid, praktis, dan mampu dalam meningkatkan kemampuan literasi matematis siswa.